Maternal low and high hemoglobin concentrations and associations with adverse maternal and infant health outcomes: an updated global systematic review and meta-analysis - Melissa F. Young; Brietta M. Oaks; Hannah Paige Rogers; Sonia Tandon; Reynaldo Martorell; Kathryn G. Dewey; Amanda S. Wendt (BMC, 2023)
Abstract Background Growing evidence suggests low and high maternal hemoglobin (Hb) concentrations may have adverse consequences for maternal and child health. There remain questions on specific Hb thresholds to define anemia and high Hb as well as how cutoffs may vary by anemia etiology and timing of assessment. Methods We conducted an updated systematic review (using PubMed and Cochrane Review) on low (< 110 g/L) and high (≥ 130 g/L) maternal Hb concentrations and associations with a range of maternal and infant health outcomes. We examined associations by timing of Hb assessment (preconception; first, second, and third trimesters, as well as at any time point in pregnancy), varying cutoffs used for defining low and high hemoglobin concentrations and performed stratified analyses by iron-deficiency anemia. We conducted meta-analyses to obtain odds ratios (OR) and 95% confidence intervals. Results The updated systematic review included 148 studies. Low maternal Hb at any time point in pregnancy was associated with: low birthweight, LBW (OR (95% CI) 1.28 (1.22-1.35)), very low birthweight, VLBW (2.15 (1.47-3.13)), preterm birth, PTB (1.35 (1.29-1.42)), small-for-gestational age, SGA (1.11 (1.02-1.19)), stillbirth 1.43 (1.24-1.65)), perinatal mortality (1.75 (1.28-2.39)), neonatal mortality (1.25 (1.16-1.34), postpartum hemorrhage (1.69 (1.45-1.97)), transfusion (3.68 (2.58-5.26)), pre-eclampsia (1.57 (1.23-2.01)), and prenatal depression (1.44 (1.24-1.68)). For maternal mortality, the OR was higher for Hb < 90 (4.83 (2.17-10.74)) than for Hb < 100 (2.87 (1.08-7.67)). High maternal Hb was associated with: VLBW (1.35 (1.16-1.57)), PTB (1.12 (1.00-1.25)), SGA (1.17 (1.09-1.25)), stillbirth (1.32 (1.09-1.60)), maternal mortality (2.01 (1.12-3.61)), gestational diabetes (1.71 (1.19-2.46)), and pre-eclampsia (1.34 (1.16-1.56)). Stronger associations were noted earlier in pregnancy for low Hb and adverse birth outcomes while the role of timing of high Hb was inconsistent. Lower Hb cutoffs were associated with greater odds of poor outcomes; for high Hb, data were too limited to identify patterns. Information on anemia etiology was limited; relationships did not vary by iron-deficiency anemia. Conclusion Both low and high maternal Hb concentrations during pregnancy are strong predictors of adverse maternal and infant health outcomes. Additional research is needed to establish healthy reference ranges and design effective interventions to optimize maternal Hb during pregnancy.